Diagnostic Value of Multiple Organ Failure on Abdominal Sepsis - Bagnulo, Homero; Bertullo, Hugo (Cirugía del Uruguay, 1983)
The diagnostic value, in the critically ill patient, of multiple organ failure of abdominal sepsis in front of the paucity of the local signs and the laboratory findings, is proposed.